Tired Judges? An Examination of the Effect of Decision Fatigue in Bail Proceedings - Torres, Luis C. (Criminal justice and behavior, 2022)
The current study begins to answer the recent call for scholars to reinvigorate the use of observational data to understand courtroom decisions. Drawing on the psychological effects of decision fatigue, the current study examines 284 bail hearing cases from two New Jersey jurisdictions to explore the role of decision fatigue on judges’ engagement, judicial deviations from prosecutors’ recommendations, and set bail amounts. The results suggest that judicial fatigue, measured as case order and session duration, limited the engagement for one judge, affected set bail amounts for both judges, and that proceeding modality may play some role in fatigue and engagement. Findings also suggest that observational data can work in tandem with administrative data to give better insight into the court process and decisions. Limitations and future research are discussed.